Wind Instruments: Brass - Jane Beethoven; Rosanne Emery; Cliff Lenz (Music magic video library, 1991)
Viewers see and hear remarkable performances on some modern brass instruments - - Learn how brass instruments produce their sound - - Hear a remarkable young tuba soloist as well as a whole ensemble of tubas - - Hear renowned artists perform in a brass quintet.